Analysis of understanding of equal nutrition knowledge among family members on a healthcare level - Didik Cahyono; Pande Ayu Naya Kasih Permatananda; Zulfayeni Zulfayeni; Ian Astarina Mas'ud (Science Midwifery, 2023)
This study aims to investigate the current state of nutrition knowledge among family members and explore the factors that influence the inequality in nutrition knowledge within households. It also aims to examine the effects of unequal nutrition knowledge on family health and propose strategies to promote equal nutrition knowledge among family members. The study was employed a mixed-methods approach, utilizing quantitative and qualitative data collection methods. The survey questionnaire was developed based on existing literature and pre-tested to ensure validity and reliability. The data collected will be analyzed using statistical software, and qualitative data will be analyzed using content analysis. The study's results provided insights into the current state of nutrition knowledge in households and the factors contributing to the inequality in nutrition knowledge. The study's findings also shed light on the effects of unequal nutrition knowledge on family health and the strategies that can be implemented to promote equal nutrition knowledge among family members. This study is significant as it can inform healthcare professionals and policymakers on the importance of nutrition education in households and encourage the promotion of healthy eating habits.